2019
DOI: 10.1007/s00393-019-0680-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in rheumatology care

Abstract: Long-term trends in rheumatology care Achievements and deficits in 25 years of the German national rheumatology database Developments in rheumatological careThe proportion of patients that visit a rheumatologist within 12 months of the onset of symptoms has increased in S66 Zeitschrift für Rheumatologie · Suppl 2 · 2019 Abstract · Zusammenfassung Z Rheumatol 2019 · 78 (Suppl 2):S65-S72 https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 25 publications
1
14
0
2
Order By: Relevance
“…In 846 patients with a physician-reported SLE diagnosis in 2016, 64% received HCQ. 6 The National Database only covers patients in rheumatological care. In the incident SLE cohort in this manuscript, only 56% of the patients had contact with a rheumatologist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 846 patients with a physician-reported SLE diagnosis in 2016, 64% received HCQ. 6 The National Database only covers patients in rheumatological care. In the incident SLE cohort in this manuscript, only 56% of the patients had contact with a rheumatologist.…”
Section: Discussionmentioning
confidence: 99%
“…National Database 6 ; however, majority of patients have long-standing disease and numbers on incident SLE cases are small. 7 8 The German LuLa study, the second relevant cohort in Germany, focuses on self-reported outcomes instead.…”
Section: Lupus Science and Medicinementioning
confidence: 99%
“…Opioids are most commonly prescribed to patients reporting severe pain in axSpA. Overall, NSAID prescriptions for RA, AS and PsA have decreased in the 2000s coinciding with the increase in biologic therapies within the NDB [30]. In contrast, other nonopioid analgesics are prescribed more frequently than before.…”
Section: Discussionmentioning
confidence: 99%
“…The results of retrospective analysis of 385 PMR patient data, made by Giollo A. et al (2019) in Italy, demonstrate "a frequent need for a protracted GC use" attending this disease and a possible protective effect of adjuvant aminobisphosphonate therapy: they were used by 60 % patients. The use of aminobisphosphonates was associated with the GC discontinuation irrespective of the age, initial Prednisone dose and osteoporosis presence (hazard ratio 0.66; 95 % CI 0.50-0.88) [38].…”
Section: Notes: Accp -Anti-cyclic Citrullinated Protein Antibodies; Ae -Adverse Effect; Ah -Arterial Hypertension; Ap -Alkaline Phosphatamentioning
confidence: 97%
“…Referring to the «treat to target» concept, i.e. treatment till the target is reached, used for PMR as a chronic condition, associated with elevated risks of various complications in the elderly people, we rely on the opinion by the Italian researchers and Mayo Clinic representatives, Camellino D. et al (2019), who consider the control of inflammatory activity, functional disorders and patient health as the treatment target, as well as maintaining the life quality in general [48].…”
Section: лекції огляди / Lectures Reviewsmentioning
confidence: 99%